Influence of the frame-type antenna on the RF-discharge peripheral plasma parameters in the Uragan-3M torsatron - Leleko, Ya.F.; Grigor’eva, L.I.; Chechkin, V.V.; Grekov, D.L. (Вопросы атомной науки и техники, 2017)
A qualitative evaluation is made of what changes of the electric potential near the frame-type antenna occur under the influence of following effects: the ponderomotive Miller force, which acts on plasma electrons near the source of radiation; the rectification of the probe oscillating potential of the RF waves, which are excited by the frame-type antenna; and the rectified potential of the antenna, which arises, when RF power is on.